Parallel Splitting for RFID tag anti-collision. (11th November 2011) - Yeh, Ming-Kuei; Jiang, Jehn-Ruey
In the Radio Frequency IDentification (RFID) system, the reader identifies tags by interrogating their IDs through a shared wireless communication channel. When multiple tags transmit their IDs to the reader simultaneously, collisions occur and the performance of tag identification degrades. In this paper, we propose a probabilistic counter-based anti-collision protocol using the idea of Parallel Splitting (PS) to reduce tag collisions. The proposed protocol also utilizes an adaptive identification-tree height adjustment mechanism to fine tune the effect of PS. We analyse and simulate the proposed protocol and compare it with related protocols to demonstrate its advantages.